2021
DOI: 10.3390/ijms22126187
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically Controlled Carbonate Nanocomposite with Ciprofloxacin for Biofilm Eradication

Abstract: Biofilms are the reason for a vast majority of chronic inflammation cases and most acute inflammation. The treatment of biofilms still is a complicated task due to the low efficiency of drug delivery and high resistivity of the involved bacteria to harmful factors. Here we describe a magnetically controlled nanocomposite with a stimuli-responsive release profile based on calcium carbonate and magnetite with an encapsulated antibiotic (ciprofloxacin) that can be used to solve this problem. The material magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
5
0
2
Order By: Relevance
“…The mechanisms of these processes are unknown. It was shown that the uptake efficiency can be modulated by NPs surface modification or by addition of various additives such as tissue homogenate S9 fraction containing cytosol and microsomes [56][57][58][59]. The synthesized composites showed moderate activity compared to free bioactive molecules, but the obtained results can be considered positive for unoptimized systems.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of these processes are unknown. It was shown that the uptake efficiency can be modulated by NPs surface modification or by addition of various additives such as tissue homogenate S9 fraction containing cytosol and microsomes [56][57][58][59]. The synthesized composites showed moderate activity compared to free bioactive molecules, but the obtained results can be considered positive for unoptimized systems.…”
Section: Discussionmentioning
confidence: 99%
“…Ferria hydrosol: Ferria hydrosol was prepared by the procedure described earlier [ 5 , 53 ]. Briefly, 2.5 g of iron (II) chloride tetrahydrate and 5 g of iron (III) chloride hexahydrate were dissolved in 100 mL of deionized water and 11 mL of ammonia was added rapidly under constant stirring.…”
Section: Methodsmentioning
confidence: 99%
“…Above all, these are exactly why bacterial biofilm related diseases, such as osteoarthritis, valvulitis, rhinitis, cystitis, vaginitis, periodontitis, specific pneumonia, otitis, etc., of which implant-associated infections are the most common, are currently the culprits of chronic infections bringing tremendous survival hazards to mankind ( Luis Del Pozo, 2018 ). While bacterial biofilms develop over the exterior of surgical implants (for example, a prosthesis of the knee joint), they tend to aggregate inflammatory compositions and secrete metabolic substances, resulting in an acidic multi-radical microenvironment, which contributes to the failure of wound healing ( Rumyantceva et al., 2021 ). Most secondary surgeries for implant removal in clinical practices are linked closely to biofilm development by Staphylococcus aureus (S. aureus) .…”
Section: Introductionmentioning
confidence: 99%